2018
DOI: 10.1002/jpen.1459
|View full text |Cite
|
Sign up to set email alerts
|

Close Relationship Between Immunological/Inflammatory Markers and Myopenia and Myosteatosis in Patients With Colorectal Cancer: A Propensity Score Matching Analysis

Abstract: Background The systemic inflammatory response (SIR) via host‐tumor interactions has been termed the seventh hallmark of cancer, and several studies demonstrated that SIR might be a pivotal mediator for progression of cancer cachexia. The objective of this study was to clarify the correlation between sarcopenia and SIR in patients with colorectal cancer (CRC). Methods A total of 308 patients with CRC were enrolled in this study. Preoperative psoas muscle mass index and intramuscular adipose tissue content were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 49 publications
3
28
0
Order By: Relevance
“…Elevated miR-203 level in pre-operative serum was an independent risk factor for myopenia in colorectal cancer patients During the last decade, various blood-based markers, such as haemoglobin, lymphocytes, and albumin, have been shown as potential analytes for the assessment of nutrition status and myopenia in patients with various malignancies. 38,39 In line with previously published evidence, our cohort also demonstrated that both pre-operative haemoglobin and albumin levels were significantly decreased in CRC patients with low vs. high PMI ( Figure S2A-S2C). To determine the potential of serum miR-203 as a predictive biomarker for myopenia, we next performed multivariate logistic analysis including these representative blood-based markers in CRC patients.…”
Section: Dysregulated Mir-203 Expression In Tissue and Serum Of Colorsupporting
confidence: 90%
“…Elevated miR-203 level in pre-operative serum was an independent risk factor for myopenia in colorectal cancer patients During the last decade, various blood-based markers, such as haemoglobin, lymphocytes, and albumin, have been shown as potential analytes for the assessment of nutrition status and myopenia in patients with various malignancies. 38,39 In line with previously published evidence, our cohort also demonstrated that both pre-operative haemoglobin and albumin levels were significantly decreased in CRC patients with low vs. high PMI ( Figure S2A-S2C). To determine the potential of serum miR-203 as a predictive biomarker for myopenia, we next performed multivariate logistic analysis including these representative blood-based markers in CRC patients.…”
Section: Dysregulated Mir-203 Expression In Tissue and Serum Of Colorsupporting
confidence: 90%
“…All DEXA studies [14,15,16] included in this review used LUNAR DPX-L & LUNAR PRODIGY software (Discovery ® , Hologic, Bedford, MA USA) for body composition measurements. Of the 20 CT studies, six studies [17,18,19,20,21,22] used Slice-O-Matic software (TomoVision, Montreal, Quebec, Canada), three studies [23,24,25] used Image J software (NIH Image J version 1.47, ), two studies [26,27] used Synapse Vincent software (Fujifilm Medical, Tokyo, Japan), two studies [28,29] used Infinitt PACS software (INFINITT Healthcare Co., Ltd, Seoul, Korea) , one study [30] used OSIRIX software (OSIRIX ®, Version 3.3, downloaded from ), one study [31] used Terrarecon software (Terarecon 3.4.2.11, San Mateo, CA, USA), one study [32] used Somatom Software (Somatom Sensation, Siemens, Fairfield, CT, USA) and manual CT images analyses was performed in four studies [33,34,35,36]. All the 20 CT studies used same thresholds for muscle (−29 to 150 HU) to measure SMA, which were normalized for height 2 to define SMI.…”
Section: Resultsmentioning
confidence: 99%
“…However, the clinical utility of landmarks other than L3 is not clear. There is some debate as to whether the measurement of psoas muscle at lumbar 3 level is less reliable and inferior to measuring all muscles at this level [42,43] and therefore, these studies [44,45] were considered separately. Using psoas muscle measurement, Hervochon and co-workers, in a cohort of 161 patients with operable NSCLC, reported that low SMI (total psoas area ≤ 33rd percentile) was significantly associated with elevated CRP [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is unknown why immunotherapy is less efficacious in patients with myosteatosis, several studies have suggested a possible association between myosteatosis, inflammation, and the efficacy of immunotherapy. The presence of myosteatosis has been reportedly associated with elevated inflammatory marker values, including those of tumor necrosis factor (TNF)‐α, interleukin (IL)‐6, the NLR, and C‐reactive protein in humans 33–35 . IL‐6 increases glucocorticoid levels in the serum, which may impair the infiltration and proliferation of CD8+ T cells within the tumor and weaken the therapeutic effects of PD‐1/PD‐L1 inhibitors 9,36 .…”
Section: Discussionmentioning
confidence: 99%